PROFILE OF CHEMOTHERAPY TREATMENT IN BREAST CANCER PATIENTS AT MOEWARDI GENERAL HOSPITAL IN 2025 - Pratama, Kharisma Jayak; Luthfiyanti, Niken; Sudarsih, Dyah Ayu (LPPM Universitas Duta Bangsa Surakarta, 2025)
Breast cancer is one of the most common types of cancer found in women, with a prevalence that continues to increase every year. Chemotherapy is one of the main therapies in the treatment of breast cancer, both as adjuvant therapy (after surgery) and neoadjuvant therapy (before surgery). Moewardi General Hospital, as a referral hospital in Central Java Province, provides chemotherapy treatment services for breast cancer patients with various drug regimens that have been proven effective. This study aims to analyze the chemotherapy treatment profile in breast cancer patients at Moewardi General Hospital in 2025. The data used in this study included the type of chemotherapy regimen, the number of patients using it, and the side effects experienced by patients. The results showed that the combination of Paclitaxel and Epirubicin was the main regimen used, with a percentage of patients reaching 30%. Common side effects include nausea, vomiting, fatigue, and a decrease in white blood cell count. Despite challenges in managing side effects, chemotherapy treatment at Moewardi General Hospital shows promising results with a high success rate. This study is expected to serve as a reference for improving the quality of breast cancer treatment at this hospital and provide insights for the development of chemotherapy therapy in the future.